2017
DOI: 10.1002/jbmr.3295
|View full text |Cite
|
Sign up to set email alerts
|

Cherubism Mice Also Deficient in c-Fos Exhibit Inflammatory Bone Destruction Executed by Macrophages That Express MMP14 Despite the Absence of TRAP+ Osteoclasts

Abstract: Currently, it is believed that osteoclasts positive for tartrate-resistant acid phosphatase (TRAPþ) are the exclusive bone-resorbing cells responsible for focal bone destruction in inflammatory arthritis. Recently, a mouse model of cherubism (Sh3bp2 KI/KI ) with a homozygous gain-of-function mutation in the SH3-domain binding protein 2 (SH3BP2) was shown to develop auto-inflammatory joint destruction. Here, we demonstrate that Sh3bp2 KI/KI mice also deficient in the FBJ osteosarcoma oncogene (c-Fos) still exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 69 publications
1
7
0
Order By: Relevance
“…Macrophages are considered to serve essential functions in RA pathogenesis because they are the main producers of pro‐inflammatory cytokines that promote inflammation . The number of synovial macrophages is correlated with the clinical disease activity, and selective macrophage depletion has a strong anti‐inflammatory effect in animal models of arthritis . Generally, M1 macrophages are pro‐inflammatory, whereas M2 macrophages are anti‐inflammatory.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Macrophages are considered to serve essential functions in RA pathogenesis because they are the main producers of pro‐inflammatory cytokines that promote inflammation . The number of synovial macrophages is correlated with the clinical disease activity, and selective macrophage depletion has a strong anti‐inflammatory effect in animal models of arthritis . Generally, M1 macrophages are pro‐inflammatory, whereas M2 macrophages are anti‐inflammatory.…”
Section: Discussionsupporting
confidence: 90%
“…(36) The number of synovial macrophages is correlated with the clinical disease activity, and selective macrophage depletion has a strong anti-inflammatory effect in animal models of arthritis. (46) Generally, M1 macrophages are pro-inflammatory, whereas M2 macrophages are anti-inflammatory. In the present study, we found that numerous M1-like macrophages accumulated in the synovium of the CIA mice, whereas JWH133 treatment obviously reduced the RA-induced increase in M1-like macrophages and enhanced the amount of M2-like macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…S1 F). Furthermore, treatment with an inhibitor specific for MT1-MMP (NSC405020; Kittaka et al, 2018) decreased podosome function to the same extent (Fig. S1 F), indicating that MT1-MMP is the predominant enzyme responsible for the observed Src-induced podosomal matrix degradation.…”
Section: Resultsmentioning
confidence: 86%
“…Analysis of the SH3BP2 cherubism mutant mice revealed that heterozygous mice exhibit osteopenia owing to increased osteoclast formation, whereas homozygous mutant mice spontaneously develop systemic organ inflammation and severe osteopenia [52]. The mutant macrophages are hypersensitive to receptor activator NF-κB ligand (RANKL) and tumor necrosis factor (TNF), leading to the production of a large number of osteoclasts [52,57,65,66,67]. In the mutant cells, accumulated SH3BP2 proteins enhance phosphorylation of SYK in response to RANKL and TNF, and subsequently activate NFATc1, which is a master regulator of osteoclastogenesis [52,57].…”
Section: Effects Of Tankyrase Inhibition On Bonementioning
confidence: 99%